2020
DOI: 10.3390/jmse8060462
|View full text |Cite
|
Sign up to set email alerts
|

Severe Coastal Hypoxia Interchange with Ocean Acidification: An Experimental Perturbation Study on Carbon and Nutrient Biogeochemistry

Abstract: Normally atmospheric CO2 is the major driver of ocean acidification (OA); however, local discharge/degradation of organic matter (OM) and redox reactions can exacerbate OA in coastal areas. In this work we study the response of nutrient and carbon systems to pH decrease in relation to hydrographically induced intermittent characteristics and examine scenarios for future ocean acidification in a coastal system. Laboratory microcosm experiments were conducted using seawater and surface sediment collected from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
(126 reference statements)
0
2
0
Order By: Relevance
“…The carbonate buffer system alleviated the decrease of pH by enhancing the outgassing of CO 2 , which further formed a positive feedback loop of water acidification in the reservoir area (Figure 9a). Previous studies indicated that more acidified conditions would promote carbonate dissolution and result in an increase in TA and HCO 3 − (Kapetanaki et al, 2018(Kapetanaki et al, , 2020. Notably, the SEM results show that pCO 2 variation has no significant impact on DIC concentration (p > 0.05), which can be attributed to the interannual variation of DIC in TGD driven by HCO 3 − generated by mineralization and water acidification, rather than the loss of DIC caused by CO 2 outgassing (Figures 9b and 9c).…”
Section: Organic Matter Degradation and Retention Effect In Wet Seasonmentioning
confidence: 99%
“…The carbonate buffer system alleviated the decrease of pH by enhancing the outgassing of CO 2 , which further formed a positive feedback loop of water acidification in the reservoir area (Figure 9a). Previous studies indicated that more acidified conditions would promote carbonate dissolution and result in an increase in TA and HCO 3 − (Kapetanaki et al, 2018(Kapetanaki et al, , 2020. Notably, the SEM results show that pCO 2 variation has no significant impact on DIC concentration (p > 0.05), which can be attributed to the interannual variation of DIC in TGD driven by HCO 3 − generated by mineralization and water acidification, rather than the loss of DIC caused by CO 2 outgassing (Figures 9b and 9c).…”
Section: Organic Matter Degradation and Retention Effect In Wet Seasonmentioning
confidence: 99%
“…The metropolitan urban center of Attiki, one of the most populated areas in the Mediterranean, is located in the northern borderland of the inner Saronikos Gulf that receives the treated sewage of the entire region, whereas in Elefsis area significant industrial and shipbuilding activities take place. Following the Water Framework Directive 2000/60 concerning the ecological status of European waters [45], extensive research and continuous monitoring of the coastal water quality in Elefsis Bay has been conducted during the last decades, based on biotic and abiotic quality criteria [46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%